"Responsible Stewards" of Classical Antiquities?: The Society for American Archaeology's "Statement on Collaboration" and Non-American Material Culture. Issue 3 (August 2022) - Marlowe, Elizabeth
ABSTRACT: This article considers the relevance of the Society for American Archaeology's 2018 "Statement on Collaboration with Responsible and Responsive Stewards of the Past" for imported antiquities (specifically, "classical" ones—that is, from Mediterranean regions). Various practical, legal, and ethical differences between collecting imported versus domestic objects make it difficult to identify "responsive and responsible stewards" of the former. An obstacle to responsible stewardship of privately owned classical collections—and to collaboration between classical archaeologists and collectors—is the 2008 acquisition guidelines issued by the two leading professional organizations in the museum field. I argue that the best home for unprovenienced and poorly provenienced antiquities collections is in university museums, where their complicated object biographies can be fully researched, taught, and displayed.